Management of temporomandibular joint recurrent dislocation using Dautery’s procedure: report and review - Bhandari, S. K.; Issar, Yuvraj; Sambyal, Shanender Singh; Navin Kumar, Andrews (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Temporomandibular joint (TMJ) dislocation is an involuntary forward movement of the mandible beyond the articular eminence with the condyle remaining stuck in the anterior-most position which leaves the patient unable to close his mouth. Various surgical methods have been described in literature for the management of TMJ dislocation in patients where conservative measures are not successful and need surgical intervention. This case report highlights outcome of Dautrey’s method of surgical correction in three cases of recurrent bilateral TMJ dislocation. All the patients had history of manual reduction of lock jaw in the past and none was medically compromised. TMJ tomograms open mouth confirmed anterior dislocation of condyles beyond articular eminence in all three patients. Total six Dautrey’s procedures were performed. All the patients showed marked improvement in pain and TMJ function with no relapse at two years follow up. Post-operative mouth opening became normal in all the patients at one year follow up. No episode of pain, clicking, deviation or TMJ dislocation was seen in follow up period of 1, 3, 6, 12, 24 months. Hence, Dautery’s procedure serves as an effective management option for recurrent temporomandibular joint dislocation.